Hubungan Kepatuhan Cuci Tangan dan Penggunaan APD Perawat dengan Resiko Kejadian Healthcare Associated Infections (HAIS) pada Masa Pandemi Covid-19 di RSUD Mayjend. H.M. Ryacudu Lampung Utara - Eka Novita Sari; M Ricko Gunawan; M Arifki Zainaro (Universitas Malahayati Lampung, 2022)
ABSTRACT: RELATIONSHIP OF HANDWASHING COMPLIANCE AND NURSE PPE USE WITH RISK OF HEALTHCARE ASSOCIATED INFECTIONS (HAIS) DURING THE COVID-19 PANDEMIC AT RSUD MAYJEN H.M. RYACUDU NORTH LAMPUNG Introduction: Infection is the invasion of the body by a pathogen or microorganism, which can cause disease or tissue damage. A hospital infection or hospital-acquired infection (HOIS) or healthcare-associated infection (HAIS) is an infection acquired during a patient's hospital stay, provided that the incubation period of the disease has not occurred at the time of admission. Objective: It is known that there is a relationship between handwashing compliance and the use of PPE for nurses with the risk of healthcare-associated infections (HAIS) during the COVID-19 pandemic at the Mayjend. H.M Ryacudu Hospital, North Lampung in 2021. Methods : The type of research used in this study is related to the descriptive nature with a cross sectional research design. The subjects of this study were all obstetrical, pediatric (perinatal and NICU) nurses, operating rooms and internal medicine at Mayjend.H.M Ryacudu Hospital, North Lampung. The number of samples used as many as 60 respondents.Results: The statistical test of nurses' compliance with the chi-square in handwashing obtained a p-value of 0.033 where the p-value (0.033 0.05) then Ha, and the Odds Ration value was accepted at 0.314. By using the chi-square statistical test for nurses who use PPE, the p-value is 0.241, so the p-value (0.241 0.05) and Ho is rejected, and the Odds ration value is 0.519.Conclusion: There is a relationship between handwashing compliance with the risk of health-related infections (HAIS), and there is no relationship between the use of PPE by nurses and the risk of healthcare-associated infections (HAIS) at the Mayjend H.M Ryacudu Hospital, North Lampung. Keywords: Compliance with handwashing, use of APD, HAIS INTISARI : HUBUNGAN KEPATUHAN CUCI TANGAN DAN PENGGUNAAN APD PERAWAT DENGAN RESIKO KEJADIAN HEALTHCARE ASSOCIATED INFECTIONS (HAIS) PADA MASA PANDEMI COVID-19 DI RSUD MAYJEND. H.M. RYACUDU LAMPUNG UTARA Pendahuluan : Infeksi adalah invasi tubuh oleh patogen atau mikroorganisme, yang dapat menyebabkan penyakit atau kerusakan jaringan. Infeksi rumah sakit atau infeksi yang didapat di rumah sakit (HOIS) atau infeksi terkait perawatan kesehatan (HAIS) adalah infeksi yang diperoleh selama pasien dirawat di rumah sakit, asalkan masa inkubasi penyakit belum berlangsung pada saat masuk. Tujuan : Diketahui hubungan kepatuhan cuci tangan dan penggunaan APD perawat dengan resiko kejadian healthcare associated infections (HAIS) pada masa pandemi covid-19 di RSUD Mayjend.H.M Ryacudu Lampung Utara.Metode : Jenis penelitian yang digunakan dalam penelitian ini berkaitan dengan sifat deskriptif dengan desain penelitian cross sectional. Subyek penelitian ini adalah seluruh perawat obstetri, anak (perinatal dan NICU), kamar operasi dan penyakit dalam di RSUD Mayjend.H.M Ryacudu Lampung Utara. Jumlah sample yang dipakai sebanyak 60 responden.Hasil : Uji statistik kepatuhan perawat terhadap chi-square dalam cuci tangan diperoleh nilai p sebesar 0,033 dimana nilai p α (0,033 0,05) kemudian Ha, dan nilai Oods Ration diterima sebesar 0,314. Dengan menggunakan uji statistik chi-square perawat yang menggunakan APD didapatkan nilai p-value 0,241, sehingga nilai p-value α (0,241 0,05) dan Ho ditolak, serta nilai Oods ration sebesar 0,519.Kesimpulan : Memiliki hubungan antara kepatuhan cuci tangan dengan risiko infeksi terkait kesehatan (HAIS), serta tidak ada hubungan antara penggunaan APD oleh perawat dengan risiko healthcare associated infections (HAIS) pada RSUD mayjend H.M Ryacudu Lampung Utara. Kata Kunci : Kepatuhan cuci tangan, penggunaan APD, HAIS